The Application of N-th Root Processing Technique on S-Wave Records - Lilik Hendrajaya (Journal of Mathematical and Fundamental Sciences, 1983)
Abstract. There are many methods to increase signal-to-noise ratio (S/N) of seismic records in order to identify the interested signals, resolve them into their components and extract any valuable information relating the source mechanism the earth's structure in which the seismic wave travel, and other seismic wave properties. In this study N-th Root processing technique is applied on S-wave data recorded at the Warramunga Seismic Array (WRA) in Northern Australia. Besides signal enhancement, arrival identification and slowness measurement are also products of this processing. Sari. Ada beberapa cara untuk menaikkan angka perbandingan isyarat dan derau (S/N) pada rekaman gelombang seismic yang berguna dalam proses mencirikan isyarat, memisahkan kelompok gelombang dan menarik beberapa informasi penting yang berhubungan dengan mekanisme sumber, struktur dalam bumi yang dilalui gelombang dan beberapa sifat gelombang seismik. Pada penelitian ini dicoba digunakan teknik akar pangkat N pada data gelombang S yang terekam pada stasiun pengamat gempa Warramunga di Australia Utara. Selain perbaikan amplitudo isyarat dihasilkan juga pencirian gelombang dan pengukurang slowness (kebalikan kecepatan) oleh pengolahan data gelombang ini.